Characterization of Integrin Molecular Tension of Human Breast Cancer Cells on Anisotropic Nanopatterns - Kim, Kyung Ah; Vellampatti, Srivithya; Kim, Byoung Choul (Frontiers in Molecular Biosciences, 2022)
Physical interactions between cells and micro/nanometer-sized architectures presented in extracellular matrix (ECM) environment significantly influence cell adhesion and morphology, often facilitating the incidence of diseases, such as cancer invasion and metastasis. Sensing and responding to the topographical cues are deeply associated with a physical interplay between integrins, ligands, and mechanical force transmission, ultimately determining diverse cell behavior. Thus, how the tension applied to the integrin-ligand bonds controls cells’ response to the topographical cues needs to be elucidated through quantitative analysis. Here, in this brief research report, we report a novel platform, termed “topo-tension gauge tether (TGT),” to visualize single-molecule force applied to the integrin-ligand on the aligned anisotropic nanopatterns. Using the topo-TGT assay, first, topography-induced adhesion and morphology of cancerous and normal cells were compared with the pre-defined peak integrin tension. Next, spatial integrin tensions underneath cells were identified using reconstructed integrin tension maps. As a result, we characterized each cell’s capability to comply to nanotopographies, magnitude of the spatial integrin tension, and the existence of ventral rupture caused by invadopodial force. Altogether, our quantitative information on integrin tension will be a valuable basis for understanding the biophysical mechanisms underlying force balance influencing adhesion to the topographical cues.